2012
DOI: 10.5805/ksci.2012.14.3.400
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pop-up Store Attributions Toward Brand Attitude and Revisiting Intention - Focus on Sports Brands -

Abstract: : This study explores the characteristics and effects of a pop-up store based on how the store attributions of a pop-up store influence brand attitude and brand patronage intention. The questionnaire consisted of 3 instruments: store attributes, brand attitude, and brand revisiting intention. Data were analyzed by factor analysis, frequency analysis, reliability analysis, and multiple regressions, using SPSS 18.0. We surveyed 123 males and females, who had an experience of a pop-up store, and interviewed five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Empirical studies of pop-up retail have mainly tapped responses of western consumers (e.g. de Lassus and Freire, 2014; Kim et al , 2010; Niehm et al , 2007; Ryu, 2011); only one study (Chae et al , 2012) of Korean consumers written in Korean has been found regarding non-western consumer response toward pop-up retail.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies of pop-up retail have mainly tapped responses of western consumers (e.g. de Lassus and Freire, 2014; Kim et al , 2010; Niehm et al , 2007; Ryu, 2011); only one study (Chae et al , 2012) of Korean consumers written in Korean has been found regarding non-western consumer response toward pop-up retail.…”
Section: Introductionmentioning
confidence: 99%